Effectiveness of Educational TV in Pakistan: A Case Study of Students of AIOU: Nazar Muhammad, M. Zafar Iqbal (PJDOL, 2023)
The research has been conducted to find out the role of TV in promoting distance education in Pakistan. The objectives of the study were a) to analyze the usefulness of educational TV for students in Pakistan b) to explore effectiveness of educational TV for students in Pakistan c) to determine access of students to educational TV in Pakistan d) to find out the problems faced by the students to use educational TV in Pakistan. Survey method of rese